TECHNOLOGY AND WELL-BEING: VOICES FROM ESP TEACHERS - Iswati, Luluk; Hastuti, Saptin Dwi Setyo (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
Although research in the use of technology for teaching ESP has increased, there is still inadequate empirical evidence that informs us on how technology affects ESP teachers’ well-being. Therefore, the purpose of this study was to investigate the impact of technology on ESP teachers’ well-being. This qualitative study collected data through semi in-depth interviews to six ESP teachers from different fields and institutions. To overcome geographical constraints, the interviews were conducted online through Zoom video conferencing. Thematic analysis was conducted based on which data were categorized and coded. The findings suggest that the use of technology in teaching has affected teachers’ well-being both positively and negatively regarding work-life balance, the changing role, workload and task efficiency. Furthermore, the overuse of technology contributes to ESP teachers’ level of stress as they encounter some challenges (digital fatigue, time management issue, scepticism about students’ work authenticity, and overwhelmed feeling), and students’ negative behaviours. Some strategies were employed to deal with the challenges. This study implies the need for strategic institutional support and adaptation to maximize its benefit and minimize negative impacts.